Waste Management In Tourist Areas Sabang City In 2023 - zubir; Ramadhan , Muhammad Teguh; Fajriansyah, Fajriansyah (ASJo: Aceh Sanitation Journal, 2023)
Community participation is one of the factors in the success of the environmental health program, where the increasing amount of waste among the community can become a threat to humans and the environment. All parties involved must be a good choice. Seeing the potential to utilize waste into creative products and services in the framework of proper waste management. One of the efforts to reduce the negative impact of plastic waste on the environment is to implement the 3R principles in everyday life, namely reduce, reuse and recycle.This study aims to find out how waste management is managed in the Tourism Area of Sabang City in 2023.This type of research is using the observation method with a descriptive study design. The method of collecting primary data is to conduct interviews with employees at the Department of Environment, Sanitation and City Beauty (DLHK) of Sabang City as many as 77 respondents using total sampling technique. The test used is descriptive analysis to find out how waste management is in the Tourism Area of Sabang City in 2023.The results of the study showed that 61.0% of waste generation did not meet the requirements, 100% did not meet the requirements for waste segregation, 97.4% met the requirements for waste collection, 100% met the requirements for waste transportation, 66.2% for waste processing. fulfill the requirements, waste disposal is 100% eligible, and elements of waste management management are 98.7% do not meet the requirements in the tourist area of Sabang City in 2023.